Analysis of Short Time Period of Operation of Horizontal Ground Heat Exchangers - Salsuwanda Selamat; Akio Miyara; Keishi Kariya (Resources, 2015)
Ground source heat pump (GSHP) systems have been proven to have higher efficiency compared to conventional air source heat pump systems for space heating and cooling applications. While vertical ground heat exchangers (GHE) are favorable in GSHP installation, this type of configuration requires higher capital costs as opposed to horizontal configuration. Numerical simulation has been used to accurately predict the thermal performance of GHE. In this paper, numerical analysis of thermal performance for slinky horizontal GHE loops in different orientations and operation modes is discussed. It was found that the loop orientation is not so important due to the little effect it has on thermal performance. While the mean heat exchange rate of copper loop increases 48% compared to HDPE loop, the analysis supports the common claim that heat exchange rate is predominantly limited by the thermal conductivity of the ground. With the same amount of circulation work, the mean heat exchange rate increases by 83%–162% when operated in parallel loops operations. The performance in these operations can be further optimized to 10%–14% increase when spacing between adjacent loops was provided. The spacing helps to minimize interference of heat flow that would penalize the overall thermal performance.